KEBUDAYAAN POTONG JARI SEBAGAI SIMBOL DUKA SUKU MONI DI DESA UGIDIMI DISTRIK BIBIDA KABUPATEN PANIAI PROVINSI PAPUA - Zonggonau, Amatus (Universitas Sam Ratulangi, 2017)
Ethnic diversity is a source of national culture. Nations is a community groups bound unity culture, language, and shelter. Hence, every ethnic groups have different languages, tradition and cultural matters is different. Papua was an island still bind closely their culture, but there are still certain areas who are still alive culture without influenced by an unfamiliar culture. Culture cut off an in the Moni tribe as an expression of grief and prevention reÃ«nacted. Cutting the fingers is depriving of the organ of body which will have an influence to health of a person. Grief when have lived away by a loved one and lost one member of family very sting.Methods used in research is to descriptive qualitative. The qualitative method as procedure research that yields data descriptive of words written or spoken of people and observable behavior. The use of the qualitative method is considered appropriate to study and understand culture cut finger based on emik.The Moni ethnic very revere tradition cut finger they as an expression of condolences and sadness is deep of members of the family left. Tradition cut finger in Papua own were conducted with various many ways, starting from using sharps like a knife, an ax or machete. There are also who did it in biting segments his finger to drop out, to bind or fasten with a rope so that the blood is halted and finger joints become dead then had only been done cutting finger.Keyword: finger, cutting, grief